Vitamin E TPGS based palatable, oxidatively and physically stable emulsion of microalgae DHA oil for infants, children and food fortification. Issue 11 (1st September 2020) - Singh, Harmanpreet; Singh, Jasvinder; Singh, Shashank K.; Singh, Narpinder; Paul, Surinder; Sohal, Harminder Singh; Gupta, Umesh; Jain, Subheet Kumar
Abstract: Clinically, Docosahexaenoic acid (DHA) has been implicated for the prevention of cognitive disorders and is considered as a vital component for normal brain development, especially in infants and children's. However, clinical uses of microalgae DHA oil are limited due to its compromised physical- and oxidative- stability along with poor organoleptic properties. Thus, in this present study, a stable and palatable pharmaceutical emulsion formulation having an extended shelf life was investigated using Vitamin E TPGS (Tocopheryl polyethylene glycol succinate) as biosurfactant. Optimized emulsion was found to have better oxidative and physical stability with lower peroxide formation and no creaming under all storage conditions. Rancimat analysis exhibited increased induction point in comparison to plain DHA oil and commercial formulation. Further, in rheological analysis better thixotropic behavior with 100% recovery of optimized emulsion was observed. Prepared emulsion was also found palatable and suitable for fortifications of juice, milk and other beverages during sensory analysis. Ex vivo intestinal permeability exhibited 2 folds increase in DHA absorption with permeability coefficient (3.83 × 10 −6 cm s −1 ) in comparison to commercial (1.75 × 10 −6 cm s −1 ). Improved in vivo pharmacodynamic activity and 1.4 folds increase in bioavailability in comparison to DHA oil during the pharmacokinetic study was observed, demonstrating the better bioavailability of Vitamin E TPGS based emulsion formulation. Thus, this study provided an insight for a pharmaceutically effective composition of DHA emulsion having extended storage shelf life, oxidative and physical stability and food fortification ability. Graphical Abstract: uf0001